Electronic properties of two-dimensional zinc oxide in hexagonal, (4,4)-tetragonal, and (4,8)-tetragonal structures by using Hybrid Functional calculation - C. Supatutkul (2018)
© Published under licence by IOP Publishing Ltd. This work reports the structures and electronic properties of two-dimensional (2D) ZnO in hexagonal, (4,8)-tetragonal, and (4,4)-tetragonal monolayer using GGA and HSE-hybrid functional. The calculated results show that the band gaps of 2D ZnO sheets are wider than those of the bulk ZnO. The hexagonal and (4,8)-tetragonal phases yield direct band gaps, which are 4.20 eV, and 4.59 eV respectively, while the (4,4)-tetragonal structure has an indirect band gap of 3.02 eV. The shrunken Zn-O bond lengths in the hexagonal and (4,8)-tetragonal indicate that they become more ionic in comparison with the bulk ZnO. In addition, the hexagonal ZnO sheet is the most energetically favourable. The total energy differences of (4,8)-tetragonal and (4,4)-tetragonal sheets from that of hexagonal monolayer (per formula unit) are 197 meV and 318 meV respectively.